Coming of Age: How JAC is Reflecting a National Research Agenda for Communications in Agriculture, Natural Resources, and Life Human Sciences - Lulu Rodriguez; James F. Evans (Journal of Applied Communications, 2016)
This study analyzed communications research trends, topics, needs, and opportunities involving agriculture, natural resources, and life and human sciences since the development of a national research agenda (NRA) in 2007. A content analysis of 23 issues of the Journal of Applied Communications (JAC) published over 7.5 years (2008 to mid-2015) examined the degree to which the articles reflected the priority research areas (PRAs), key research questions (KRQs), and priority initiatives (PIs) identified in the NRA. Findings showed a watershed period from 2011-2014 in which the journal produced an average of 18 articles per year. The first RPA (RPA A), “Enhancing decision making within the agricultural sectors of society,” received the most attention, followed by RPA B, which focused on rural-urban interactions. Within RPA A, the largest number of articles addressed the key research question, “What are the most effective ways to identify and communicate information that has economic and social value?” Under this question, the priority initiative (PI), “Analyze and strengthen the effectiveness of communications content and methods in communicating information,” garnered the most research attention. Findings showed a dearth of studies in PIs across the four RPAs, including economic returns to, and social impacts of, agricultural information; how to engage key interest groups in decision making; models of collaboration, negotiation, and conflict management; use of critical theory in analyzing agriculture and related communications; the interplay between data, information and meaning within stakeholders; information asymmetries and barriers to public participation in decision making; the mechanisms by which information is made available; if and how knowledge gains value; and ethical issues and standards. Results prompted seven suggestions for further research progress and direction.
Keywords: Agricultural Communications; Research Agendas; Research Themes; Research Needs; Journal of Applied Communications